The relationship of simple sum and Divisia monetary aggregates with real GDP and inflation: a wavelet analysis for the US - Michael Scharnagl; Martin Mandler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We apply wavelet analysis to compare the relationship between simple sum and Divisa monetary aggregates with real GDP and CPI infl ation for the U.S. using data from 1967 to 2013. Wavelet analysis allows to account for variations in the relationships both across the frequency spectrum and across time. While we find evidence for a weaker comovement of Divisia compared to simple sum monetary aggregates with real GDP the relationship between money growth and infl ation is estimated to be much tighter between Divisia monetary aggregates and CPI infl ation than for simple sum aggregates, in particular at lower frequencies. Furthermore, for the Divisia indices for broader monetary aggregates (M2, M2M, MZM) we estimate a stable lead before CPI in flation of about four to five years.
Keywords: C30; E31; E40; 330